Verbal Encouragement and Between-Day Reliability During High-Intensity Functional Strength and Endurance Performance Testing - Engel, Florian A.; Faude, Oliver; Kölling, Sarah; Kellmann, Michael; Donath, Lars (Frontiers in Physiology, 2019)
As verbal encouragement (VE) is used in high intensity functional exercise testing, this randomized controlled crossover study aimed at investigating whether VE affects high intensity functional strength and endurance performance testing. We further examined between-day variability of high intensity functional strength and endurance performance testing with and without VE. Nineteen experienced athletes (seven females and 12 males, age: 23.7 ± 4.3 years) performed a standardized one repetition maximum (1 RM) squat test and a 12-min high-intensity functional training (HIFT) workout [as many repetitions as possible (AMRAP)] on four different days over a 2-week period. Athletes randomly performed each test twice, either with VE or without (CON), with a minimum of 72 h rest between tests. Very good to excellent relative between-day reliability with slightly better values for strength testing (ICC: 0.99; CV: 3.5–4.1%) compared to endurance testing (ICC 0.87–0.95; CV: 3.9–7.3%) were observed. Interestingly, VE led to higher reliability during endurance testing. Mean squat strength depicted higher strength values with VE (107 ± 33 kg) compared to CON (105 ± 33 kg; p = 0.009, Cohen’s d: 0.06). AMRAP in the endurance test showed negligible differences between VE (182 ± 33 AMRAP) and CON (181 ± 35 AMRAP; p = 0.71, Cohen’s d: 0.03). In conclusion, the effects of VE do not notably exceed day-to-day variability during high intensity functional strength (CV: 3.5–4.1%) and endurance (CV: 3.9–7.3%) testing. However, high intensity functional strength and endurance testing with VE seems to be slightly more reliable, particularly during endurance testing.